Discovering your roots : an introduction to genealogy - Colletta, John Philip, 1949-; Teaching Company (2014)
This course of 15 half-hour lectures by Professor Colletta presents different procedures for locating sources of ancestors' records in America.
Interviewing kin and mining home sources -- Genealogy online--gems and junk -- The library--shelves full of family history -- Military service and homestead records -- How to build historical context -- Your ancestors in ship passenger lists -- Your ancestors in naturalization records -- The genealogical proof standard -- Your ancestors in the county courthouse -- Your ancestors in state records -- How to write biography -- Dos and don'ts of writing history -- Seaching in your ancestors' backyards -- Assembling an account of your discoveries -- Extending your family tree overseas.
Includes bibliographical references in course guidebook.
Professor John Philip Colletta, lecturer.
Keywords: United States -- Genealogy -- Sources; United States -- Emigration and immigration -- Archival resources